Method for preparing spinnable mesophase pitch from coal liquefaction pitch

Through the extraction of coal liquefied asphalt and thermal polymerization of crystalline nuclear method, the problems of high prices, complex processes and low purity of mesophase asphalt raw materials are solved, and low cost and high purity mesophase asphalt preparation is achieved, suitable for high-performance asphalt carbon fibers production.

CN119193183APending Publication Date: 2024-12-27SHANDONG CHENYANG NEW CARBON MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550971.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the raw materials of mesophase asphalt have high prices, complex processes, high investment costs, and low purity, making it difficult to meet the requirements of high-performance bituminous carbon fibers.

Method used

The coal liquefied asphalt is dissolved and extracted by extraction agent, and purified pure aromatic asphalt raw materials are obtained through distillation, and high-quality mesophatic asphalt is obtained through thermal polymerization of crystal nucleus method. The impurity content is reduced by extraction agent and crystal nucleus technology, and the molecular distribution is increased by narrower degree and spinability.

Benefits of technology

The preparation of mesophase asphalt with low cost, low ash content and high purity is achieved, the process flow is simplified, the equipment and investment costs are reduced, and high-performance spunable mesophase asphalt is obtained, which is suitable for the preparation of high-performance asphalt carbon fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115066090000091
    Figure BDA0005115066090000091
Patent Text Reader

Abstract

The invention relates to a method for preparing spinnable mesophase pitch by using coal liquefaction pitch, which comprises the following specific preparation steps: mixing a coal liquefaction pitch raw material and a compound solvent in a dissolving kettle, uniformly heating, stirring and dissolving, and separating in a horizontal spiral filter centrifuge with filter cloth to obtain supernatant liquid; performing negative-pressure distillation on the supernatant liquid to obtain pure aromatic asphalt, crushing the pure aromatic asphalt and crystal nucleus, uniformly mixing in proportion, and adding into a negative-pressure high-temperature reaction kettle to perform thermal polymerization reaction to obtain the mesophase asphalt. Compared with the prior art, the method has the following beneficial effects that the raw materials are simple and easy to obtain, the equipment process is simple, large-scale industrialization is extremely easy, the investment is small, the cost is low, in addition, by introducing the crystal nucleus, the reaction activation energy can be reduced, and finally the intermediate phase content gt is obtained; 99% of mesophase pitch with high spinnability is a high-quality raw material for preparing high-performance pitch carbon fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of mesophase asphalt preparation methods, and specifically relates to a method for preparing low-ash, high-quality spinnable mesophase asphalt by utilizing pure aromatic hydrocarbons extracted from coal liquefaction asphalt. Background Art

[0002] High-performance asphalt-based carbon fibers have very stringent requirements on the raw material spinning-grade mesophase asphalt, which requires the mesophase asphalt to have few heteroatoms, low ash content, high aromaticity, low condensation degree, neatly arranged aromatic macromolecules, high carbon yield, good fluidity and good spinnability.

[0003] At present, domestic mesophase asphalt is usually made of coal tar or petroleum residue as raw materials. The composition of coal tar and petroleum residue is complex and unstable, and contains trace impurities that are not easy to remove, which directly affects the properties of mesophase asphalt. In view of the inherent defects of coal tar asphalt and petroleum residue asphalt, some researchers use pure aromatic compounds (naphthalene, anthracene) as raw materials, add anhydrous AlCl3 or HF / BF3, and use catalytic method to prepare mesophase asphalt. However, the catalyst AlCl3 has strong polarity and cannot be effectively removed. The catalyst HF / BF3 has strong acidity and seriously corrodes the equipment. In addition, the catalyst method has low yield and high cost. The ash content of mesophase asphalt synthesized in China is generally >500ppm, which is far from the foreign Japanese and American technologies. The ash content of coal-based mesophase asphalt in Japan and oil-based mesophase asphalt in the United States is ≤50ppm. Up to now, low-ash spinning-grade mesophase asphalt in China has not been commercialized.

[0004] Coal liquefaction process will produce a byproduct rich in aromatics, coal liquefaction pitch. The polycyclic aromatic hydrocarbon compounds in coal liquefaction pitch are hydrogenated products with moderate C / H and low nitrogen and sulfur content. In theory, they are ideal raw materials for preparing mesophase pitch. Compared with pure aromatics such as polyacrylonitrile and refined naphthalene, which are the main raw materials for preparing high-performance carbon fibers at home and abroad, coal liquefaction pitch, a byproduct of coal liquefaction processing, is cheaper and has a richer source. However, due to the complex composition of coal liquefaction pitch, which contains straight-chain hydrocarbons, aromatic hydrocarbon components and high-molecular-weight condensed ring hydrocarbon components, if it is used directly, the molecular weight distribution after polymerization is too wide, and the polymerization mesophase conversion is insufficient, making it difficult to obtain mesophase pitch that has both high anisotropy and good solubility and low softening point.

[0005] Therefore, in order to solve one of the above problems, it is necessary to develop a method for preparing mesophase asphalt with simple and easily available raw materials, simple equipment and process, and low investment cost. Summary of the invention

[0006] In view of the above deficiencies in the prior art, the technical problem to be solved by the present invention is: to provide a method for preparing mesophase asphalt using pure aromatic hydrocarbons extracted from coal liquefaction asphalt, so as to solve the problems of high raw material prices, complex processes, high investment costs, low purity of mesophase asphalt, etc.

[0007] The method for preparing spinnable mesophase asphalt from coal liquefaction asphalt of the present invention adopts an extractant to dissolve and extract the coal liquefaction asphalt, distills to obtain purified pure aromatic asphalt raw material, and then obtains high-quality mesophase asphalt through further crystal nucleus thermal polymerization and small molecule removal.

[0008] The specific steps are as follows:

[0009] S1: obtaining a pure aromatic asphalt raw material through dissolution, extraction and distillation with an extractant: mixing a high-ash coal liquefaction asphalt raw material and an extractant in a dissolution kettle, uniformly heating, stirring and dissolving, and then entering a horizontal screw filter centrifuge with a filter cloth for separation to obtain a supernatant, and finally distilling the supernatant through negative pressure to obtain a high-quality mesophase raw material, wherein the mesophase raw material is a 6-7-ring pure aromatic asphalt;

[0010] The compounded solvent can form new hydrogen bonds with coal liquefaction asphalt, destroy the original cross-linking structure in the raw coal liquefaction asphalt, and specifically extract 6-7 ring aromatic hydrocarbons in the coal liquefaction asphalt. At the same time, the dissolution of macrocyclic aromatic hydrocarbons, aliphatic hydrocarbons and other heteroatom substances is reduced through compounding.

[0011] S2: Obtaining intermediate phase asphalt by crystal nucleus thermal polymerization: The pure aromatic asphalt and crystal nuclei obtained in step S1 are crushed, uniformly mixed according to proportion, and added into a negative pressure high temperature reactor for thermal polymerization reaction, and N2 stirring reaction is carried out throughout the reaction process.

[0012] The mesophase, as a liquid crystal-like component, is a compound with a certain crystal structure. The heterogeneous nucleation technology is used to induce the orderly growth of the raw asphalt around the mesophase nucleus, which promotes the formation and development of the anisotropic structured mesophase. At the same time, it can reduce the activation energy of the polymerization reaction, promote the formation and growth of the anisotropic phase, and help to generate a spinnable mesophase asphalt with an anisotropic structure content of >99%, adjustable softening point, narrow molecular distribution, and excellent rheological properties.

[0013] Preferably, the extractant in step S1 is a composite solvent, which is a composite solvent of an organic solvent containing a C=O bond and an aromatic solvent, the organic solvent containing a C=O bond is one of propyl acetate, acetone, and cyclohexanone, and the aromatic solvent is one of benzene, toluene, and pyrobenzene.

[0014] Preferably, the compound solvent in step S1 is a compound solvent of propyl acetate and toluene, and the mass ratio of propyl acetate to toluene is 3:0-1.

[0015] Preferably, in the compounded solvent in step S1, the mass ratio of propyl acetate to toluene is 3:0.5.

[0016] Preferably, the mass ratio of the compounded solvent to the coal liquefaction asphalt in step S1 is 5 to 2:1;

[0017] Preferably, the mass ratio of the compounded solvent to the coal liquefaction asphalt in step S1 is 4:1.

[0018] Preferably, the dissolving temperature in step S1 is 35-60°C.

[0019] Preferably, the dissolving temperature in step S1 is 45°C.

[0020] Preferably, the dissolution time in step S1 is 2 to 6 hours.

[0021] Preferably, the dissolution time in step S1 is 3 hours.

[0022] Preferably, the stirring rate of the stirring and dissolving in step S1 is 75-150 r / min.

[0023] Preferably, the centrifugal speed of the horizontal screw filter centrifuge in step S1 is 3500-5000 r / min, and the mesh size of the centrifugal filter cloth is 450-500 meshes.

[0024] Preferably, in step S1, pure aromatic asphalt raw material is recovered by negative pressure distillation, and the softening point of the pure aromatic asphalt is 85-90°C, the ash content is <20ppm, and the molecular weight is 350-400. The molecular weight can be analyzed and tested by gel chromatography, and the molecular structure can be detected by gas chromatography-mass spectrometry.

[0025] Preferably, the crystal nucleus in step S2 is low-ash mesophase asphalt with an ash content of ≤20ppm, and is one of naphthalene-based mesophase asphalt, coal-based mesophase asphalt or oil-based mesophase asphalt.

[0026] Preferably, the crystal nucleus in step S2 is naphthalene-based mesophase pitch.

[0027] Preferably, in step S2, the pure aromatic asphalt is crushed to <1 mm, and the crystal nuclei are crushed to <0.2 mm.

[0028] Preferably, the amount of the crystal nuclei added in step S2 is 0.1 to 3 wt % of the amount of pure aromatic asphalt.

[0029] Preferably, the amount of the crystal nuclei added in step S2 is 1 wt% of the amount of pure aromatic asphalt.

[0030] Preferably, the polymerization temperature of the thermal polymerization reaction in step S2 is 375°C to 400°C.

[0031] Preferably, the polymerization temperature of the thermal polymerization reaction in step S2 is 385°C to 390°C.

[0032] Preferably, the polymerization negative pressure of the thermal polymerization reaction in step S2 is 7-10Kp.

[0033] Preferably, the initial amount of N2 gas in the N2 stirring reaction in step S2 is 100L / (kg 沥青 ·h), when the polymer softening point is 210℃-220℃ and the mesophase content is 70%, increase the initial amount of N2 gas to 140L / (kg 沥青 h).

[0034] Preferably, the polymerization stirring speed of the thermal polymerization reaction in step S2 is 60-100 r / min, and the polymerization insulation time is 10-20 h.

[0035] Preferably, the polymerization insulation time of the thermal polymerization reaction in step S2 is 15 to 20 hours.

[0036] The product obtained by the preparation method of the present invention is observed under a polarizing microscope. The content of the intermediate phase formed therein is preferably >98% depending on the polymerization time. The softening point thereof is tested to be 275-285°C using a needle penetration method. The ash content is <50ppm using a combustion weighing method. The intermediate phase asphalt obtained is spun by a 24-hole spinning machine to obtain high-quality intermediate asphalt fibers with a fiber diameter of 10-17μm.

[0037] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0038] (1) Low cost: Different from the traditional AlCl3 catalytic polymerization method, the technical solution of the present invention is to extract and separate the widely available coal liquefaction pitch to obtain pure aromatic substances with low ash content, with high purification accuracy; and the solvent used in the purification process has a low boiling point and can be directly recycled and reused, without the output of hazardous waste products; the raw materials are simple and easy to obtain, the equipment process is simple, and it is very easy to scale up for industrialization, with small investment and low cost;

[0039] (2) The pure aromatic asphalt obtained by the technical solution of the present invention has a similar molecular structure to the pure asphalt obtained by conventional catalytic polymerization, and contains only 6-7 ring pure aromatic molecules, with a narrower molecular weight distribution and a mainly planar molecular structure, which is beneficial to the subsequent mesophase asphalt polymerization regulation and mesophase generation;

[0040] (3) The technical solution of the present invention can reduce the activation energy of the reaction by introducing crystal nuclei, and finally obtain a highly spinnable mesophase asphalt with an mesophase content of >99%. This asphalt has high optical anisotropy and a moderate softening point. At the same time, it has a narrow molecular weight distribution after polymerization and can be directly spun without other modification treatments. It is a high-quality raw material for preparing high-performance asphalt carbon fibers. DETAILED DESCRIPTION

[0041] The present invention is further described below by means of specific embodiments, but the present invention is not limited thereto. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0042] Embodiment 1:

[0043] (1) Preparation of pure aromatic asphalt raw materials:

[0044] First, a compound solvent is added into a dissolving kettle, wherein the compound solvent is a compound solvent of propyl acetate and toluene, and the mass ratio of propyl acetate to toluene is 3:0.5. Then, a high-ash coal liquefaction asphalt raw material is crushed to less than 1 mm, and the mass ratio of the compound solvent to the coal liquefaction asphalt is 4:1. The raw material is added into the dissolving kettle while stirring, and the stirring frequency is 100 r / min. The temperature is raised to 45°C. After dissolving and extracting for 4 hours, the stirring is stopped, and the material is pumped into a horizontal spiral filtering centrifuge from the bottom of the kettle for separation. The centrifugal speed is 4500 r / min, and the pore size of the centrifugal filter cloth is 450 meshes. The supernatant is obtained by centrifugation; the supernatant is pumped into a negative pressure distillation kettle, and the pure aromatic asphalt raw material is extracted from the bottom of the distillation tower. The distillation adopts negative pressure distillation, and the negative pressure is controlled at -50Kpa to -70Kpa. By controlling the different temperatures at the top of the tower, propyl acetate and toluene solvents are respectively extracted, and after heat exchange, they are transported to a solvent recovery tank for reuse.

[0045] (2) Preparation of high-quality mesophase asphalt:

[0046] 49.5 kg of pure aromatic asphalt was crushed to <1 mm, and 0.5 kg of naphthalene mesophase asphalt with an ash content of 20 ppm was crushed to <0.2 mm. The two materials were fully mixed and added into a 100 L negative pressure polymerization reactor. The temperature in the reactor was raised to 380 ° C at a heating rate of 1 ° C / min, and the stirring rate was adjusted to 80 r / min to ensure that the materials were fully mixed. During the heating process, the amount of N2 was maintained at 5m 3 / h, and continue the reaction for about 10h, until the needle penetration softening point of the polymer reaches 212℃ and the mesophase content is about 70%, then increase the amount of N2 to 7m 3 / h, and continue the reaction for 7h, until the final polymer ring softening point is 280℃, and polarized light shows that the mesophase content is >99%, thus obtaining the final spinning mesophase asphalt; finally, the prepared mesophase asphalt is spun through a 24-hole spinning machine, and the spinning temperature is controlled to obtain high-quality intermediate asphalt fibers with an average fiber diameter of 11.2μm.

[0047] Embodiment 2:

[0048] (1) Preparation of pure aromatic asphalt raw materials:

[0049] First, a compound solvent is added into a dissolving kettle, wherein the compound solvent is a compound solvent of propyl acetate and toluene, and the mass ratio of propyl acetate to toluene is 3:0.5. Then, a high-ash coal liquefaction asphalt raw material is crushed to less than 1 mm, and the mass ratio of the compound solvent to the coal liquefaction asphalt is 4:1. The raw material is added into the dissolving kettle while stirring, and the stirring frequency is 100 r / min. The temperature is raised to 45°C. After dissolving and extracting for 4 hours, the stirring is stopped, and the material is pumped into a horizontal spiral filtering centrifuge from the bottom of the kettle for separation. The centrifugal speed is 4500 r / min, and the pore size of the centrifugal filter cloth is 450 meshes. The supernatant is obtained by centrifugation; the supernatant is pumped into a negative pressure distillation kettle, and the pure aromatic asphalt raw material is extracted from the bottom of the distillation tower. The distillation adopts negative pressure distillation, and the negative pressure is controlled at -50Kpa to -70Kpa. By controlling the different temperatures at the top of the tower, propyl acetate and toluene solvents are respectively extracted, and after heat exchange, they are transported to a solvent recovery tank for reuse.

[0050] (2) Preparation of high-quality mesophase asphalt:

[0051] 48.5 kg of pure aromatic asphalt was crushed to <1 mm, and 1.5 kg of naphthalene mesophase asphalt with an ash content of 20 ppm was crushed to <0.2 mm. The two materials were fully mixed and added into a 100 L negative pressure polymerization reactor. The temperature in the reactor was raised to 380 ° C at a heating rate of 1 ° C / min, and the stirring rate was adjusted to 80 r / min to ensure that the materials were fully mixed. During the heating process, the amount of N2 was maintained at 5m 3 / h, and continue the reaction for about 10 hours until the needle penetration softening point of the polymer reaches 220°C and the mesophase content is about 70%. Then increase the amount of N2 to 7m 3 / h, and continue the reaction for 7h, until the final polymer ring softening point is 285℃, and polarized light shows that the mesophase content is >99%, thus obtaining the final mesophase asphalt for spinning; finally, the prepared mesophase asphalt is spun through a 24-hole spinning machine, and the spinning temperature is controlled to obtain high-quality intermediate asphalt fibers with an average fiber diameter of 12.6μm.

[0052] Embodiment 3:

[0053] (1) Preparation of pure aromatic asphalt raw materials:

[0054] First, a compound solvent is added into a dissolving kettle, wherein the compound solvent is a compound solvent of propyl acetate and toluene, and the mass ratio of propyl acetate to toluene is 3:1. Then, a high-ash coal liquefaction asphalt raw material is crushed to less than 1 mm, and the mass ratio of the compound solvent to the coal liquefaction asphalt is 4:1. The raw material is added into the dissolving kettle while stirring, and the stirring frequency is 100 r / min. The temperature is raised to 45°C. After dissolving and extracting for 4 hours, the stirring is stopped, and the material is pumped into a horizontal spiral filtering centrifuge from the bottom of the kettle for separation. The centrifugal speed is 4500 r / min, and the pore size of the centrifugal filter cloth is 450 meshes. The supernatant is obtained by centrifugation; the supernatant is pumped into a negative pressure distillation kettle, and the pure aromatic asphalt raw material is extracted from the bottom of the distillation tower. The distillation adopts negative pressure distillation, and the negative pressure is controlled at -50Kpa to -70Kpa. By controlling the different temperatures at the top of the tower, propyl acetate and toluene solvents are respectively extracted, and after heat exchange, they are transported to a solvent recovery tank for reuse.

[0055] (2) Preparation of high-quality mesophase asphalt:

[0056] 49.5 kg of pure aromatic asphalt was crushed to <1 mm, and 0.5 kg of naphthalene mesophase asphalt with an ash content of 20 ppm was crushed to <0.2 mm. The two materials were fully mixed and added into a 100 L negative pressure polymerization reactor. The temperature in the reactor was raised to 380 ° C at a heating rate of 1 ° C / min, and the stirring rate was adjusted to 80 r / min to ensure that the materials were fully mixed. During the heating process, the amount of N2 was maintained at 5m 3 / h, and continue the reaction for about 10 hours. When the needle penetration softening point of the polymer reaches 218°C and the mesophase content is about 70%, the amount of N2 is increased to 7m 3 / h, and continue the reaction for 5h, until the final polymer ring softening point is 283℃, and polarized light shows that the mesophase content is >99%, thus obtaining the final spinning mesophase asphalt; finally, the prepared mesophase asphalt is spun through a 24-hole spinning machine, and the spinning temperature is controlled to obtain high-quality intermediate asphalt fibers with an average fiber diameter of 12.1μm.

[0057] Embodiment 4:

[0058] (1) Preparation of pure aromatic asphalt raw materials:

[0059] First, a compound solvent is added into a dissolving kettle, wherein the compound solvent is a compound solvent of propyl acetate and toluene, and the mass ratio of propyl acetate to toluene is 3:0.5. Then, a high-ash coal liquefaction asphalt raw material is crushed to less than 1 mm, and the mass ratio of the compound solvent to the coal liquefaction asphalt is 4:1. The raw material is added into the dissolving kettle while stirring, and the stirring frequency is 100 r / min. The temperature is raised to 45°C. After dissolving and extracting for 4 hours, the stirring is stopped, and the material is pumped into a horizontal spiral filtering centrifuge from the bottom of the kettle for separation. The centrifugal speed is 4500 r / min, and the pore size of the centrifugal filter cloth is 450 meshes. The supernatant is obtained by centrifugation; the supernatant is pumped into a negative pressure distillation kettle, and the pure aromatic asphalt raw material is extracted from the bottom of the distillation tower. The distillation adopts negative pressure distillation, and the negative pressure is controlled at -50Kpa to -70Kpa. By controlling the different temperatures at the top of the tower, propyl acetate and toluene solvents are respectively extracted, and after heat exchange, they are transported to a solvent recovery tank for reuse.

[0060] (2) Preparation of high-quality mesophase asphalt:

[0061] 49.5 kg of pure aromatic asphalt was crushed to <1 mm, and 0.5 kg of naphthalene mesophase asphalt with an ash content of 20 ppm was crushed to <0.2 mm. The two materials were fully mixed and added into a 100 L negative pressure polymerization reactor. The temperature in the reactor was raised to 380 ° C at a heating rate of 1 ° C / min, and the stirring rate was adjusted to 80 r / min to ensure that the materials were fully mixed. During the heating process, the amount of N2 was maintained at 5m 3 / h, and continue the reaction for about 10 hours. When the needle penetration softening point of the polymer reaches 218°C and the mesophase content is about 70%, the amount of N2 is increased to 7m 3 / h, and continue the reaction for 7h, until the final polymer ring softening point is 280℃, and polarized light shows that the mesophase content is >99%, thus obtaining the final mesophase asphalt for spinning; finally, the prepared mesophase asphalt is spun through a 24-hole spinning machine, and the spinning temperature is controlled to obtain high-quality intermediate asphalt fibers with an average fiber diameter of 11.8μm.

[0062] Example 5: A pure aromatic mesophase pitch obtained by catalytic synthesis and sold in a certain city was subjected to 24-hole spinning. Under the optimal spinning conditions, fibers with an average filament diameter of 13.5 μm were obtained.

[0063] Performance Testing

[0064] The coal liquefaction pitch raw materials and mesophase pitch in Examples 1-4 were respectively taken and their softening points Sp, toluene insoluble matter TI, quinoline insoluble matter QI, coking value and ash content were tested.

[0065] The pure aromatic asphalt prepared in Examples 1-4 was taken respectively, and a commercially available naphthalene asphalt was taken as a control, and the softening point Sp, toluene insoluble matter TI, quinoline insoluble matter QI, coking value, ash content, number average molecular weight and weight average molecular weight were tested respectively, and the molecular structure was determined at the same time.

[0066] The above results are shown in Table 1 below.

[0067] Table 1 Asphalt analysis results

[0068]

[0069] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

[0070] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing spinnable mesophase pitch using coal liquefaction pitch, characterized in that: The specific steps are as follows: S1: Mixing high-ash coal liquefaction pitch raw material and extractant in a dissolving kettle, uniformly heating, stirring and dissolving, and then entering into a horizontal screw filter centrifuge with filter cloth for separation to obtain a supernatant, and finally distilling the supernatant through negative pressure to obtain a high-quality mesophase raw material, wherein the mesophase raw material is a 6-7 ring pure aromatic asphalt; S2: The pure aromatic asphalt and the crystal nuclei obtained in step S1 are crushed, mixed evenly in proportion, added into a negative pressure high-temperature reactor for thermal polymerization, and N2 stirring reaction is carried out throughout the reaction process to obtain the intermediate phase asphalt.

2. The method for preparing spinnable mesophase pitch using coal liquefaction pitch according to claim 1, characterized in that: The extractant in step S1 is a compound solvent, which is a compound solvent of an organic solvent containing a C=O bond and an aromatic solvent. The organic solvent containing a C=O bond is one of propyl acetate, acetone, and cyclohexanone, and the aromatic solvent is one of benzene, toluene, and pyrobenzene.

3. The method for preparing spinnable mesophase pitch using coal liquefaction pitch according to claim 2, characterized in that: The compound solvent in step S1 is a compound solvent of propyl acetate and toluene, and the mass ratio of propyl acetate to toluene is 3:0-1.

4. The method for preparing spinnable mesophase pitch using coal liquefaction pitch according to claim 3, characterized in that: In the compounded solvent in step S1, the mass ratio of propyl acetate to toluene is 3:0.

5.

5. The method for preparing spinnable mesophase pitch from coal liquefaction pitch according to any one of claims 1 to 4, characterized in that: The mass ratio of the compounded solvent to the coal liquefaction asphalt in the step S1 is 2-5:

1.

6. The method for preparing spinnable mesophase pitch using coal liquefaction pitch according to claim 5, characterized in that: The mass ratio of the compound solvent to the coal liquefaction asphalt in the step S1 is 4:

1.

7. The method for preparing spinnable mesophase pitch from coal liquefaction pitch according to claim 6, characterized in that: In the step S1, the dissolution temperature is 35-60° C., the dissolution time is 2-6 hours, and the stirring rate of the dissolution is 75-150 r / min.

8. The method for preparing spinnable mesophase pitch from coal liquefaction pitch according to claim 7, characterized in that: The centrifugal speed of the horizontal screw filter centrifuge in step S1 is 3500-5000 r / min, and the mesh number of the centrifugal filter cloth is 450-500 mesh.

9. The method for preparing spinnable mesophase pitch using coal liquefaction pitch according to claim 8, characterized in that: The crystal nucleus in step S2 is low-ash mesophase asphalt, with an ash content of ≤20ppm, and is one of naphthalene-based mesophase asphalt, coal-based mesophase asphalt or oil-based mesophase asphalt.

10. The method for preparing spinnable mesophase pitch from coal liquefaction pitch according to claim 9, characterized in that: The crystal nucleus in step S2 is naphthalene-based mesophase asphalt, the amount of the crystal nucleus added is 1wt% of the amount of pure aromatic asphalt, the polymerization temperature of the thermal polymerization reaction is 385°C to 390°C, the polymerization negative pressure is 7~10Kp, the polymerization stirring speed is 60~100r / min, and the polymerization insulation time is 10~20h.